Unusual Skin Metastasis from Gastric Cancer: A Case Report - Vicky Sumarki Budipramana (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Skin metastasis from gastric cancer are relatively rare, but they have important clinical significance because they usually indicate a worse prognosis. Skin metastasis from gastric cancer may spread through lymphatic ducts, blood vessels in the ligamentum teres, contiguous extension, or embryologic remnants of the umbilicus. Purpose: To report an unusual skin metastasis from gastric cancer that clinically resembles as a benign lesion of skin papules. Case: A rare metastasis from gastric cancer origin in a 61-year-old male in the abdominal skin. Gastric cancer metastasis in an unusual site such as the abdominal skin often resembles as dermatitis, especially in the early course of metastatic spreading, which looked like common papules on the skin. Discussion: In the beginning, the skin papules were not suspected to be a metastatic process because there was no palpable or no tenderness in the subcutan or fascia underneath. The appearance resembled common dermatitis. However, as papules rapidly spread to the surrounding skin, the malignancy was then suspected. The incisional biopsy from the papules was performed and showed that it was metastatic diffuse-type gastric adenocarcinoma. Conclusion:  The skin metastasis was different from general nodules, but rather as skin papules of general dermatitis in initial appearance. The surgeon and dermatologist should be alert if they find any benign appearance of a skin lesion on the abdominal wall in a patient with a history of gastric cancer surgery.